Imaging of IgG4-related disease of the head and neck. Issue 1 (January 2018) - Thompson, A.; Whyte, A.
Abstract : IgG4-related disease is a systemic, inflammatory disorder typically involving multiple organ systems. Several eponymous conditions described previously in the clinical and radiology literature are now recognised to be part of the IgG4-related disease spectrum. This includes multiple manifestations in the head and neck region, which are the subject of this review. Imaging can occasionally suggest the specific diagnosis of IgG4 disease. More commonly, it will be included in a limited differential diagnosis that requires clarification with the aid of image-guided biopsy. There are strict histopathological criteria for the diagnosis of IgG4-related disease.